Retaining Early Childhood Education Workers: A Review of the Empirical Literature. Issue 4 (1st October 2016) - Totenhagen, Casey J.; Hawkins, Stacy Ann; Casper, Deborah M.; Bosch, Leslie A.; Hawkey, Kyle R.; Borden, Lynne M.
ABSTRACT: Low retention in the child care workforce is a persistent challenge that has been associated with negative outcomes for children, staff, and centers. This article reviews the empirical literature, identifying common correlates or predictors of retention for child care workers. Searches were conducted using several databases, and articles that presented quantitative or qualitative data on retention for center-based child care workers in the United States were reviewed in detail. Seven themes emerged as potential predictors of retention: wages and benefits, job satisfaction, organizational characteristics, alternative employment opportunities, demographic characteristics, job characteristics, and education and training. Although some of the findings were mixed, increased retention was generally associated with the following: working in a publicly operated or nonprofit center that meets accreditation or policy standards, being older, maintaining a higher-level position, having more tenure and experience, receiving higher wages, and reporting higher job satisfaction. Based on these studies, child care centers should seek to increase pay, recruit staff with more experience, and aim to improve job satisfaction among staff to help increase retention. In addition, government-funded professional development incentive programs may help child care centers meet the goals of a high-quality, educated, and stable workforce.